(3GdeONd aj UfGYI CMcGe GdfLhes - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s ((3eOjfI GdCScfOQjI s)
(3ChdgG (B:s
(3Efi LeYJ ai gPG GdcJGH ef CMhGd UfGYI GdCMcGe hLedJgG hGdWQjb Edi GdJUQa ajgG hESJYeGdgG heG XffJg cGajkG ai eYfGg s
(3BNQgG (B:s
( (3hfNJe GdebGdg GdQGHYI HgPG GdHGH , hGdcJGH HgPg GdebGdI , hGdMeO ddg QH GdYGdejf (B) (3hHYO gPG LOGhd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HfGg CQHY ebGdGJs
(3YdjgG ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs